Analysis of the Legal Liability of Bankrupt Developers as a Form of Fulfilling Consumer Rights in Apartment Unit Sale and Purchase Disputes (Case Study of Decision No. 4716 K/Pdt/2023) - Kartika Pangestu; Moody Rizky Syailendra Putra (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
The increasing demand for vertical housing amidst limited urban land has driven the rise of apartment developments with a pre-sale system, but this model often leads to default issues by developers. The case between PT Multi Karya Utama Abadi (MKUA) and Nina Herlina in the Bandung Technoplex Living (BTL) project shows that consumers have made full payments but have not received the handover of the unit, while the developer is experiencing financial difficulties, making it difficult to implement the legally binding decision. This study aims to analyze the judge's ratio decidendi in Decision Number 4716 K/Pdt/2023 based on Article 1239 of the Civil Code and examine the form of legal responsibility of developers through the Suspension of Debt Payment Obligations (PKPU) mechanism. The study uses normative legal methods with a statutory approach, a conceptual approach, and a case approach through an analysis of related decisions at the first, appeal, and cassation levels. The results show that the judge stated that the developer had broken his promise and was obliged to compensate for losses, but settlement could not be carried out partially because the default issue was related to the company's financial failure. Therefore, PKPU is a relevant mechanism to ensure the fulfillment of consumer rights through debt restructuring that involves all creditors proportionally, thus functioning as a dual instrument for business rescue and legal protection for consumers.